Periodontal disease and cardiovascular disease: umbrella review - Heber Isac Arbildo-Vega; Fredy Hugo Cruzado-Oliva; Franz Tito Coronel-Zubiate; Joan Manuel Meza-Málaga; Sara Antonieta Luján-Valencia; Eduardo Luján-Urviola; Adriana Echevarria-Goche; Carlos Alberto Farje-Gallardo; Tania Belú Castillo-Cornock; Katherine Serquen-Olano; Tania Padilla-Cáceres; Luz Caballero-Apaza; et al. (BMC, 2024)
Abstract Background Periodontal disease (PD) is an infectious and inflammatory condition that affects the tissues surrounding and supporting the teeth. It has been suggested that PD may be associated with cardiovascular disease (CVD), one of the leading causes of mortality worldwide. Our study aimed to investigate the association between PD and CVD through an umbrella review. Methods A comprehensive search was conducted until April 2024 across various electronic databases, including PubMed, Cochrane Library, Scopus, SciELO, Web of Science, Google Scholar, ProQuest Dissertations and Theses, and OpenGrey. Systematic reviews with or without meta-analysis were considered for inclusion, without any limitations on time or language, provided they examined primary studies linking PD with CVD. The AMSTAR-2 tool was employed to assess the quality and overall confidence of the included studies. Results After the initial search, a total of 516 articles were identified. Following the application of selection criteria, 41 articles remained for further consideration. All these studies indicated an association between PD and CVD, with odds ratios and risk ratios ranging from 1.22 to 4.42 and 1.14 to 2.88, respectively. Conclusions Systematic reviews with high overall confidence support the association between PD, tooth loss, and cardiovascular diseases. However, it is crucial to interpret these results with caution due to methodological limitations. The potential public health relevance justifies preventive and corrective oral health strategies. Additionally, the need for rigorous future research is highlighted to strengthen the evidence and guide effective public health strategies.